Directory of medical and health care libraries in the United Kingdom and Republic of Ireland - Linton, William D. (Library Association, 1986)
Geographical listing. Each entry gives descriptive information such as type of library, readers, holdings, and classification. Indexes of personal names, establishments, countries, and special collections. 1st ed., 1957; 5th ed., 1982.